2010
DOI: 10.1007/s11064-010-0151-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Salvianolic Acid B in Microglia Contributes to its Neuroprotective Effect

Abstract: This study examined whether Salvianolic acid B (Sal B), a major active component of Chinese herb Radix Salviae Miltiorrhizae, may exert an anti-inflammatory effect in microglia and may be neuroprotective by regulating microglial activation. Our results showed that Sal B significantly reduced the production of nitric oxide (NO), tumor necrosis factor-alpha (TNF-alpha), interleukin-1beta (IL-1beta) and reactive oxygen species (ROS) induced by lipopolysaccharide (LPS) treatment in rat primary microglia in a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…SalB has been shown to provide anti-inflammatory, antioxidant, and neuroprotective activity by regulating microglial activation [17,35] . According to recent studies, besides functioning as a monoaminergic neurotransmitter, neuroinflammation may also have a key role in the pathogenesis of MDD [13,36] .…”
Section: Discussionmentioning
confidence: 99%
“…SalB has been shown to provide anti-inflammatory, antioxidant, and neuroprotective activity by regulating microglial activation [17,35] . According to recent studies, besides functioning as a monoaminergic neurotransmitter, neuroinflammation may also have a key role in the pathogenesis of MDD [13,36] .…”
Section: Discussionmentioning
confidence: 99%
“…There is an accumulation of evidence that Sal B may exert cardiovascular protecting effects through inhibition of oxidative stress [17] and lipid peroxidation [18], reducing the generation of ROS, increasing the release of NO, inhibition of platelet aggregation and adhesion [19], anti-inflammatory activity [20] and suppression of apoptosis induced by other factors. Thus, although there is still no direct evidence of Sal B involved in modulating lipid metabolism and improving dyslipidemia, we want to know whether Sal B could improve the cholesterol transport.…”
Section: Discussionmentioning
confidence: 99%
“…SalB, the main bioactive component of S. miltiorrhiza, was reported to protect against the ischemia-reperfusion induced injury in rat brain in vivo (Chen et al, 2000. It has also been demonstrated to inhibit lipopolysaccharide-induced inflammatory molecule expression (Lin et al, 2007;Wang et al, 2010). Inhibition of neuroinflammation may represent a novel mechanism of action of antidepressant treatment (Catena-Dell'Osso et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Salvianolic acid B (SalB, the chemical structure as shown in Fig. 1), the most abundant and bioactive compounds extracted from Labiatae, Laminaceae (Salvia miltiorrhiza) (Zhou et al, 2005), has been demonstrated to have anti-inflammatory and neuroprotective activities in vivo and in vitro (Wang et al, 2010). The phenolic hydroxyl group in the structure of SalB may be related to anti-inflammatory and antioxidant activities (Ho and Hong, 2011).…”
Section: Introductionmentioning
confidence: 99%